Identifying late Carboniferous sanukitoids in Hala’alate Mountain, Northwest China: new constraint on the closing time of remnant ocean basin in West Junggar - Li, G.; Li, Y.; Wang, Xuan-Ce; Yang, G.; Wang, R.; Xiang, K.; Liu, J.; Tong, L. (Taylor & Francis Inc., 2016)
Volcanic rocks in the Hala’alate and Aladeyikesai formations, which are composed of basaltic andesite and pyroxene andesite, are widespread in Hala’alate Mountain, West Junggar, Northwest China. These rocks (plagioclase + clinopyroxene/olivine) formed in the late Carboniferous and show a remarkable geochemical affinity with typical sanukitoids with oversaturated SiO2 (52.9–56.9 wt.%) and high MgO (3.47–6.88 wt.%, Mg# >48) contents. They also exhibit a narrow range of Sr-Nd-Pb isotopes within (87Sr/86Sr)i = 0.7037–0.7041, εNd(t) = 4.4–6.2, 206Pb/204Pb = 18.22–18.41, 207Pb/204Pb = 15.48–15.52, 208Pb/204Pb = 37.99–38.30. Hala’alate Formation volcanic rocks are similar to the sanukitoids of Karamay, with high Sr (633.5–970.1 ppm), Ba (268.7–796.3 ppm), and Sr/Y (61.34–84.28), formed by partial melting of the mantle metasomatized by slab-derived adakitic melts. In contrast, Aladeyikesai Formation volcanic rocks show some affinity with sanukitoids of the Hatu area and the Setouchi Volcanic Belt, with low Sr (442.2–508.7 ppm), Ba (199.2–485.1 ppm), and Sr/Y (25.03–30.28), generated by the partial melting of subducting sediments. Identification of late Carboniferous sanukitoids in Hala’alate Mountain provides important constraints on the closing time of the remnant ocean basin in West Junggar, and implies that multi-stage subduction–accretionary orogeny plays a crucial role in the evolution and growth of the continental crust in the Central Asian Orogenic Belt.